TiO2 Photocatalyst Nanoparticle Separation: Flocculation in Different Matrices and Use of Powdered Activated Carbon as a Precoat in Low-Cost Fabric Filtration - Carlos F. Liriano-Jorge; Ugur Sohmen; Altan Özkan; Holger Gulyas; Ralf Otterpohl (Advances in Materials Science and Engineering)
Separation of photocatalyst nanoparticles is a problem impeding widespread application of photocatalytic oxidation. As sedimentation of photocatalyst particles is facilitated by their flocculation, the influence of common constituents of biologically pretreated wastewaters (NaCl, NaHCO3, and their combination with humic acid sodium salt) on flocculation was tested by the pipet method. Results showed that the impact of these substances on TiO2 nanoparticle flocculation is rather complex and strongly affected by pH. When humic acid was present, TiO2 particles did not show efficient flocculation in the neutral and slightly basic pH range. As an alternative to photocatalyst separation by sedimentation, precoat vacuum filtration with powdered activated carbon (PAC) over low-cost spunbond polypropylene fabrics was tested in the presence of two PAC types in aqueous NaCl and NaHCO3 solutions as well as in biologically treated greywater and in secondary municipal effluent. PAC concentrations of ≥2 g/L were required in order to achieve a retention of nearly 95% of the TiO2 nanoparticles on the fabric filter when TiO2 concentration was 1 g/L. Composition of the aqueous matrix and PAC type had a slight impact on precoat filtration. PAC precoat filtration represents a potential pretreatment for photocatalyst removal by micro- or ultrafiltration.